Segmental vitiligo/Peripubertal hypopigmented pityriasis versicolor. - Bonifazi, E. (European Journal of Pediatric Dermatology, 2012)
White spots unilaterally distributed on the trunk can appear first time during summertime in peripubertal age. They can be due to segmental vitiligo or hypopigmented pityriasis versicolor.